ERGO-MECHANICAL APPLICATIONS IN SMALL-SCALE SMAW WELDING TABLE DESIGN - Bawa Susana, I Gede; Alit Triadi, Anak Agung; Kawirian, Wisnu (Universitas Negeri Semarang, 2024)
SMAW (shielded metal arc welding) is widely used in almost all types of welding work, including small industries. In small industries, workers doing SMAW welding work are generally done by squatting. This work posture causes musculoskeletal complaints in workers as a result of unnatural work postures. To overcome this is done through ergo-mechanical applications to create aids in the form of welding tables. Ergonomically based on worker anthropometric data, while mechanically with the selection of strong, lightweight, and affordable materials in terms of cost. The results of testing the welding table design based on ergo-mechanical applications provided a decrease in musculoskeletal disorders in workers. Workers' musculoskeletal disorders can be reduced by 24.61%. From the moderate category, an average of 51.6, to the light category, with an average of 38.9. The ergo-mechanical application will produce work tools that are comfortable for workers to use and meet technical standards related to specifications as a description of the technical characteristics of a work tool.